Study on the Application of Human Chorionic Gonadotropin (hCG) in Dairy Cow Superovulated with Pregnant Mare Serum Gonadotropin - Monoclonal Antibody (PMSG-MoAb) Anti PMSG - Iman Supriatna; Tuty Laswardi Yusuf; Bambang Purwantara; Gozali Moekti; Lies Parede Hernomoadi (Media Veteriner, 1998)
The research was planned to yield the biologic potential synergism of MoAb-hCG in increasing the embryo number. Twenty five dairy cows were divided into five groups. The Control Group was superovulated with 2,500 IU PMSG intramuscularly (i.m.), the remaining of the Group II, III, IV and V consecutively after being superovulated by 2,500 IU PMSG were treated with MoAb intravenously (i.v.), hCG i.v., MoAb-hCG i.v. and MoAb i.v-hCG i.m. Data evaluation were analyzed using ANOVA and LSD test. The result showed that there were increasing in number of transferable embryo per donor produced (P<0.01) after application with either MoAb i.v. (9.6), hCG i.v. (9.4), MoAb-hCG i.v. (11.2), or MoAb i.v.-hCG i.m. (9.6). The Control Group produced only 2.4 embryo per donor. The combined MoAb and hCG in one treatment were not able to increase the embryo yield (P>0.05).Key words: MoAb, PMSG, hCG, superovulation, donor, embryo